MEMAHAMI PASSION DAN PILIHAN JURUSAN DI PERGURUAN TINGGI UNTUK MENDUKUNG KARIR DI MASA DEPAN: WORKSHOP KARIR SMA MASEHI KUDUS, INDONESIA - Wijayanti, Sari; Poluan, Stevi Jimry; Nisa, Rizka Fathkin (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
The phenomenon of difficulty in finding a job causes high school graduates to become more selective in choosing college majors. However, many students still make mistakes in choosing a major, influencing low learning motivation and career problems in the labor market. This Program of Community Service (PkM) is designed to enable students of class XII Masehi Kudus High School to identify their passion, strengthen their self-identity and self-efficacy, and choose a major that fits their interests and capabilities. Observation, interview, and pre-test and post-test to the participants of the workshop are included in this activity. The findings of the analysis revealed an increase in the awareness of participants in knowing themselves, courage in speaking out their opinions, and choosing majors according to potential and interest. The program received positive feedback and is likely to be a viable model in guiding students in making the right choice of majors to enable future careers